A Typology of Factors Influencing Seniors' Participation in Strength Training in Gyms and Fitness Centers - Pettigrew, Simone; Burton, Elissa; Farrier, K.; Hill, Anne-Marie; Bainbridge, Elizabeth; Lewin, Gill; Airey, P.; Hill, Keith (Human Kinetics Inc, 2018)
Older people are less likely to engage in strength training than their younger counterparts, despite the substantial benefits of this form of exercise for preventing and addressing age-related physical decline. In many countries, strength training programs are available for older people yet are undersubscribed. The aim of this study was to identify the factors influencing older people's participation in strength training at gyms and fitness centers to provide insights into potentially effective recruitment and retention strategies for this population. A total of 79 individuals from four stakeholder groups (seniors, fitness center instructors and managers, health practitioners, and those involved in policy) were interviewed to identify and explicate relevant factors. A detailed typology was developed that provides insights into potential strategies at five ecological system levels: intrapersonal, interpersonal, organizational, social, and policy. The typology can be used as a tool for identifying opportunities to encourage strength training participation among older people.